Built on sand: Egypt's questionable strategy for growth and development - Stephan Roll; Matthias Sailer (Stiftung Wissenschaft und Politik (SWP), 2015)
The Egypt Economic Development Conference staged at the Red Sea resort of Sharm el Sheikh from 13 to 15 March will showcase the country's investment potential. Cairo hopes to prove it has started a turnaround after four years of political and economic turmoil. In fact a recovery is not even on the horizon. Foreign capital will be crucial for the mega-projects the Sisi administration is relying upon to stimulate growth. But the flow of direct investment is as uncertain as the development approach itself is questionable. With economic stagnation and an ensuing deterioration of living conditions foreseeable, protests are liable to flare up again. Germany and the European Union should prepare for further destabilisation in the Arab world's most populous nation. (SWP-Comments)
Keywords: 320